ANALISIS MANAJEMEN RISIKO KHUSUS STRUKTUR BAWAH PADA PROYEK PEMBANGUNAN GEDUNG BERTINGKAT DI KOTA JAYAPURA - Helen Giandita Wayangkau; Fandy Novrian Mangeke (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2022)
Some of the work on the substructure of the building, namely foundations (pile, bore pile, sole), soil excavation, pile cap and sloof, raft foundation, retaining wall, waterproofing, backfill and compaction. Based on the implementation method, the sub-building structure has complex and complex work characteristics, so it is very vulnerable to the occurrence of risks in the construction implementation. The PROMETHEE method is used in research to follow up the Risk Breakdown Structure method in order to obtain a comprehensive or comprehensive rating of the main risks in a project. The results showed that the unpredictable external risks, namely inflation/price increases and the decline in people's purchasing power are the highest potential risks. Risk mitigation related to inflation/price increases should be carried out more slowly at the beginning of the project because inflation is national. Then wait until the economy improves and if funds are still available, all materials can be purchased or contracted firs